Rare polyandry and common monogamy in the firefly squid, Watasenia scintillans - Noriyosi Sato (Nature Portfolio, 2020)
Abstract In cephalopods, all species are considered to be polyandrous because of their common life history and reproductive traits reflecting a polyandrous mating system. Contrary to this belief, here we show several lines of evidence for monogamy in the firefly squid, Watasenia scintillans. In this species, females are capable of long-term storage of spermatangia, and of egg spawning even after the complete disappearance of males following the breeding season. The stored spermatangia are distributed equally between bilateral pouches under the female’s neck collar. Such a nonrandom pattern of sperm storage prompted us to hypothesize that females might engage in lifetime monandry. Hence, we genotyped female-stored spermatangia and offspring, and found that in 95% of females (18/19), all the spermatangia had been delivered from a single male and all the embryos in a clutch had been sired by spermatozoa from stored spermatangia. In males, throughout the reproductive season, relative testis mass was much smaller in W. scintillans than in all other cephalopods examined previously. The mean number of male-stored spermatophores was ~ 30, equivalent to only 2.5 matings. Our genetic, demographic and morphometrical data agree with a mathematical model predicting that monogyny is favored when potential mates are scarce. Together, these results suggest mutual monogamy in W. scintillans.